2021
DOI: 10.48550/arxiv.2101.02251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-Free Assortment Pricing with Transaction Data

Abstract: We study a problem in which a firm sets prices for products based on the transaction data, i.e., which product past customers chose from an assortment and what were the historical prices that they observed.Our approach does not impose a model on the distribution of the customers' valuations and only assumes, instead, that purchase choices satisfy incentive-compatible constraints. The individual valuation of each past customer can then be encoded as a polyhedral set, and our approach maximizes the worst-case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…While we are able to leverage some ideas from this literature such as the use of ellipsoids and projected knowledge sets, we highlight, however, that the nature of the problem studied here is substantially different from the contextual pricing/search literature due to the nature of the feedback, as there is no control in our setting on the feedback one sees. The recent studies Feng et al (2018) and Chen et al (2021) study robust assortment and price optimization based on revealed preferences associated with choice data. Additional early works that focus on learning utility functions from revealed preferences include Beigman and Vohra (2006), Zadimoghaddam and Roth (2012), Balcan et al (2014), Amin et al (2015).…”
Section: Related Literaturementioning
confidence: 99%
“…While we are able to leverage some ideas from this literature such as the use of ellipsoids and projected knowledge sets, we highlight, however, that the nature of the problem studied here is substantially different from the contextual pricing/search literature due to the nature of the feedback, as there is no control in our setting on the feedback one sees. The recent studies Feng et al (2018) and Chen et al (2021) study robust assortment and price optimization based on revealed preferences associated with choice data. Additional early works that focus on learning utility functions from revealed preferences include Beigman and Vohra (2006), Zadimoghaddam and Roth (2012), Balcan et al (2014), Amin et al (2015).…”
Section: Related Literaturementioning
confidence: 99%